Urachal adenocarcinoma – case report and literature review - Petrović, Milan; Vasić, Vladimir; Janković-Veličković, Ljubinka; Šterović, Srdjan; Pejčić, Tomislav; Hadži-Djokić, Jovan (Vojnosanitetski pregled, 2020)
Introduction. Urachal adenocarcinoma is extremely rare and comprises from 0.35% to 0.7% of all bladder tumors. The most common histologic subtype of urachal tumors is adenocarcinoma which can be associated with intestinal metaplasia and mucin production. Case report. We report a case of a 53-year-old patient who attented a urologist because of an intermittent haematuria lasting for three months. The ultrasound examination detected infiltration of the bladder at the fundus, 24 × 29 mm in diameter. By the same wall, next to the tumor, there was an oval hypoechoic lesion about 40 mm in diameter. Computed tomography scan showed a solid, echogenic, strictly limited tumor at the fundus of the bladder, anteriorly, 32 × 35 × 22 mm in diameter which was positive after contrast application. The patient underwent partial cystectomy with complete excision of the tumor lesion 1.5 cm in healthy tissue. Histopathological analysis showed diagnosis of Adenocarcinoma mucinosum vesicae urinariae infiltrans. Patohistological findings detected a part of the urachal wall with a thin layer of fibromuscular tissue, chronic inflammation, microcalcifications in the lumen, flattened and desquamated epithelium. One year after the surgery, there were no signs of primary disease or metastases in other organs. Conclusion. Urachal adenocarcinoma is extremely rare. Long term survival could be achieved by surgical treatment in the early stage of the disease which consists of complete resection of urachal carcinoma and partial or total cystectomy.